A haemovigilance team provides both significant financial and quality benefits in a University Hospital. Issue 2 (April 2017) - Decadt, Ine; Costermans, Els; Van de Poel, Maai; Kesteloot, Katrien; Devos, Timothy
Abstract: Background: Haemovigilance is the process of surveillance of blood transfusion procedures including unexpected hazards and reactions during the transfusion pathway in both donors and recipients. The haemovigilance team aims to increase blood transfusion safety and to decrease both morbidity and mortality in donors and recipients. The team collects data about transfusion reactions and incidents, instructs the involved health workers and assures the tracing of blood components. The haemovigilance team at the University Hospitals Leuven has played a pioneering role in the development of haemovigilance in Belgium Although the literature about safety and quality improvements by haemovigilance systems is abundant, there are no published data available measuring their financial impact in a hospital. Therefore, we studied the costs and returns of the haemovigilance team at the University Hospitals Leuven. Material and methods: This study has a descriptive explorative design. Research of the current costs and returns of the haemovigilance team were based upon data from the Medical Administration of the hospital. Data were analyzed descriptively. Results: The haemovigilance team of the University Hospitals Leuven is financially viable: the direct costs are covered by the annual financial support of the National Public Health Service. The indirect returns come from two important tasks of the haemovigilance team itself: correction of the electronic registration of administered blood component and improvement of the return of conform preserved blood components to the blood bank. Discussion: Besides safety and quality improvement, which are obviously their main goals, the haemovigilance team also implies a financial benefit for the hospital.